PENINGKATAN HASIL BELAJAR MATA PELAJARAN PEMPROGRAMAN CNC DASAR MENGGUNAKAN SOFTWARE SIMULASI SWANSOFT SINUMERIK 802Se/C - Setiawan, Agus (Journal of Mechanical Engineering Learning, 2014)
Destination of this research is how to use this software simulation swansoft able to improve the practice of 3 grade students on courses machining base CNC use CNC machine type Sinumerik 802Se/c turning. The population was 3 grade students of Machinical Engineering Education skill courses totaling 62 of 2 class. Methods of data collection using the documentation and performance test also observation sheet. The result showed that there was an incrase in students learning outcomes pre-test score was 6,38 after initially getting treatment increased by 7,76. This is in contrast with the control group increased pre-test score 6,33 to 6,99. The result of the test T post-test obtained t = 12,024 for practice. Therefore,Â  tcount=10,943 > ttable = 1,67. Therefore, the implementation software simulation swansoft would make a better outcome to the students.